2004
DOI: 10.1016/s1090-3801(03)00087-9
|View full text |Cite
|
Sign up to set email alerts
|

Children's ratings of the intensity and unpleasantness of post‐operative pain using facial expression scales

Abstract: This study explored whether global unidimensional self-report pain scales based on facial expression help children separately estimate the sensory and affective magnitude of post-operative pain. Ninety paediatric elective surgery patients (in two age groups: 5-9 and 10-15 years) used each of four scales to estimate pain intensity and pain affect during the first 2 days after surgery. The four scales were: Faces Pain Scale (FPS), Facial Affective Scale (FAS), and the Coloured Analogue Scale (CAS) (one for inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 21 publications
(33 reference statements)
2
40
0
1
Order By: Relevance
“…8,9 In the remainder of the studies, the majority of the instruments whose psychometric qualities were being assessed used ordinal scales, i.e., they categorize attributes and establish a sequential order based on the characteristics of the attribute measured. 6 It should be pointed out that, although ordinal scales are less precise than interval scales, they are generally used with children to obtain self-reported pain assessments since they are easier for children to understand, as is the case of the Oucher Faces Scale, 10 the Faces Pain Scale (FPS) 11,12 and the Facial Affective Scale (FAS). 11 Nevertheless, in the course of this literature review it was found that ordinal scales are also used by trained observers or by the medical and nursing teams to assess child pain.…”
Section: Measurement Scales Of the Instruments Analyzedmentioning
confidence: 99%
See 4 more Smart Citations
“…8,9 In the remainder of the studies, the majority of the instruments whose psychometric qualities were being assessed used ordinal scales, i.e., they categorize attributes and establish a sequential order based on the characteristics of the attribute measured. 6 It should be pointed out that, although ordinal scales are less precise than interval scales, they are generally used with children to obtain self-reported pain assessments since they are easier for children to understand, as is the case of the Oucher Faces Scale, 10 the Faces Pain Scale (FPS) 11,12 and the Facial Affective Scale (FAS). 11 Nevertheless, in the course of this literature review it was found that ordinal scales are also used by trained observers or by the medical and nursing teams to assess child pain.…”
Section: Measurement Scales Of the Instruments Analyzedmentioning
confidence: 99%
“…6 It should be pointed out that, although ordinal scales are less precise than interval scales, they are generally used with children to obtain self-reported pain assessments since they are easier for children to understand, as is the case of the Oucher Faces Scale, 10 the Faces Pain Scale (FPS) 11,12 and the Facial Affective Scale (FAS). 11 Nevertheless, in the course of this literature review it was found that ordinal scales are also used by trained observers or by the medical and nursing teams to assess child pain. In these cases the following instruments were used: the Objective Pain Scale (OPS), 8 the Faces, Leg, Activity, Cry and Consolability scale (FLACC), 8,[13][14][15] the Children's Hospital of Eastern Ontario Pain Scale (CHEOPS), 8 the Pediatric Pain Profile (PPP), 16 the Alder Hey Triage Pain Score (AHTPS), 17 the Child Facial Coding System (CFCS) 18 and the Non-Communicating Children's Pain Checklist-Revised (NCCPC-R).…”
Section: Measurement Scales Of the Instruments Analyzedmentioning
confidence: 99%
See 3 more Smart Citations